2021
DOI: 10.1080/09637486.2021.1941804
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet – promotion and dissemination of healthy eating: proceedings of an exploratory seminar at the Radcliffe institute for advanced study

Abstract: The traditional Mediterranean diet is considered the world's most evidence-based eating pattern for promoting health and longevity. However, institutional food environments and their busy consumers often sacrifice health benefits for the convenience of faster and cheaper foods that generally are of lower quality and are more processed, and thus, contribute to the current epidemics of obesity and diabetes. Expert consensus has even identified the Mediterranean diet as the easiest to follow among healthy eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Several studies have shown that children and adolescents are the main consumers of ultra-processed foods [ 50 , 51 ], with caloric intake mainly from UPFs: 67% in the US in 2018 in 2- to 19-year-olds [ 52 ] and 65.8% in the UK in 4- to 10-year-olds [ 53 ], even in Mediterranean based countries [ 54 ]. In France, analysis of data in the INCA3 study (1- to 10-year-olds; n = 1035) suggests that 45.5% of calories came from UPFs in 2014–2015, which is an increase compared to INCA1 (1998–1999; 42.8%) and INCA2 (2006–2007; 43.2%) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that children and adolescents are the main consumers of ultra-processed foods [ 50 , 51 ], with caloric intake mainly from UPFs: 67% in the US in 2018 in 2- to 19-year-olds [ 52 ] and 65.8% in the UK in 4- to 10-year-olds [ 53 ], even in Mediterranean based countries [ 54 ]. In France, analysis of data in the INCA3 study (1- to 10-year-olds; n = 1035) suggests that 45.5% of calories came from UPFs in 2014–2015, which is an increase compared to INCA1 (1998–1999; 42.8%) and INCA2 (2006–2007; 43.2%) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also includes varying amounts of fish, moderate to high amounts of alcohol (red wine in particular), dairy products, and relatively little meat [especially red meat [ 27 ]. Evidence for the preventive impact of the Mediterranean diet on cardiovascular illnesses is growing in observational and intervention studies [ 30 , 31 ]. Intervention studies have shown that the Mediterranean diet decreases risk factors of cardiovascular disease and death in people who have previous myocardial infarctions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food availability is one of factors leading to a worsening of dietary habits [ 8 ]. The Mediterranean diet is characterized by the intake of specific food varieties, especially wholegrains, olive oil, dairy products, bread, fruits and vegetables [ 9 ]. Caprara [ 10 ] also revealed that Mediterranean diet adherence combined with high levels of physical activity helped to increase life expectancy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%